The Role of Quality Management in Improving Competitiveness and Performance of Moroccan Organizations - Omar Taouab; Soumaya Outellou (European Scientific Journal, ESJ, 2020)
This paper focuses on introducing the term “quality management” and to showcase its relationship with ISO 9000 certification, as well as its impact on competitiveness and performance of Moroccans organizations. A research method strategy was used, which began with some assumptions on the subject. This was followed by the collection of theoretical and empirical data which helped uncover new information and created a better understanding of the topic.